2004
DOI: 10.1529/biophysj.104.046128
|View full text |Cite
|
Sign up to set email alerts
|

ATP Hydrolysis in the βTP and βDP Catalytic Sites of F1-ATPase

Abstract: The enzyme F1-adenosine triphosphatase (ATPase) is a molecular motor that converts the chemical energy stored in the molecule adenosine triphosphate (ATP) into mechanical rotation of its gamma-subunit. During steady-state catalysis, the three catalytic sites of F1 operate in a cooperative fashion such that at every instant each site is in a different conformation corresponding to a different stage along the catalytic cycle. Notwithstanding a large amount of biochemical and, recently, structural data, we still … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

19
113
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(132 citation statements)
references
References 58 publications
(93 reference statements)
19
113
0
Order By: Relevance
“…An attractive explanation for the production of this species is the extensively discussed possibility of transfer (direct or indirect) of a proton from the attacking water molecule to an oxygen of the ␥-phosphate group (9,16,17,(35)(36)(37), a mechanism that has been called substrate-assisted catalysis (16). Such proton transfer can be direct or mediated via water molecules, as has been discussed for Ras and the F1 ATPase reaction (4,38). After attack of the generated hydroxyl ion on phosphorus and cleavage of the ␤,␥-bond, H 2 PO 4 Ϫ would be generated as the initial product.…”
Section: Resultsmentioning
confidence: 99%
“…An attractive explanation for the production of this species is the extensively discussed possibility of transfer (direct or indirect) of a proton from the attacking water molecule to an oxygen of the ␥-phosphate group (9,16,17,(35)(36)(37), a mechanism that has been called substrate-assisted catalysis (16). Such proton transfer can be direct or mediated via water molecules, as has been discussed for Ras and the F1 ATPase reaction (4,38). After attack of the generated hydroxyl ion on phosphorus and cleavage of the ␤,␥-bond, H 2 PO 4 Ϫ would be generated as the initial product.…”
Section: Resultsmentioning
confidence: 99%
“…Single-molecule studies showed that the 120°rotational steps can be further divided into approximately 90°and 30°substeps during hydrolysis (7, 10). A roughly 2-ms waiting time is observed between these substeps, most likely due to two separate 1-ms steps, one corresponding to the hydrolysis or synthesis step, the other to P i release or binding (10).Considering the function of the ATP synthase, structure determinations (12-16), mutation studies on the α-, β-, and γ-subunits (1, 17-20), single-molecule studies (6, 7, 10), and simulations (11,(21)(22)(23)(24)(25)(26)(27)) have contributed to a rather detailed understanding of its mode of mechanical action. However, one of several issues that need to be better characterized (1) is the mechanistic resolution of the chemical reaction steps on the way from ADP to ATP at an atomic level.…”
mentioning
confidence: 99%
“…Considering the function of the ATP synthase, structure determinations (12)(13)(14)(15)(16), mutation studies on the α-, β-, and γ-subunits (1,(17)(18)(19)(20), single-molecule studies (6,7,10), and simulations (11,(21)(22)(23)(24)(25)(26)(27)) have contributed to a rather detailed understanding of its mode of mechanical action. However, one of several issues that need to be better characterized (1) is the mechanistic resolution of the chemical reaction steps on the way from ADP to ATP at an atomic level.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This positional shift of the a-subunit makes the well-conserved arginine residue in the a-subunit, known as ''Arg-finger,'' very close to the c-phosphate of ATP in the range of a few Ås (4). Although some biochemical experiments and simulations have indicated that the Arg-finger accelerates the ATP hydrolysis rate by stabilizing the transition state (5,6), it is dispensable for the rotary catalysis (7). The ATP hydrolysis step is not thought to be a major torque-generating step, because accompanying conformational change appears to be too small to induce rotation of the csubunit.…”
Section: Torque Generation Mechanism Of F 1 As Suggested From the Crymentioning
confidence: 99%